The ability of changes in oct angiography values to predict visual field and retinal nerve layer tomography progression in patients with glaucoma progression: A prospective study - Suleyman Demir; Mehmet Talay Koylu; Alper Can Yılmaz (Photodiagnosis and Photodynamic Therapy, 2024)
Introduction: To investigate whether changes in optical coherence tomography angiography (OCTA) values can predict progression in the visual field (VF) and retinal nerve fiber layer (RNFL) in patients with glaucoma progression. Methods: All patients in the glaucoma outpatient clinic of SBU Gulhane Medicine Faculty between 2021 and 2023 underwent RNFL, 24:2 VF, and simultaneous peripapillary OCTA. 130 eyes that progressed were included in the study. Thinning of more than 5 μ in any quadrant in the RNFL or a decrease of more than 1 dB in the MD value in the visual field within 6 months was accepted as a progression criterion. The ability of changes in OCTA thickness values and OCTA radial peripapillary capillary plexus (RPCP) analysis to predict progression in RNFL and VF was prospectively investigated. Results: The mean age of the patients was 66.9 ± 11.8 years. There was progression in VF in 70 eyes and RNFL in 89 eyes between baseline and 6-month controls. The change in OCTA thickness values had insufficient ability to predict the progression of RNFL in the superior, inferior, nasal, temporal and total quadrants (p = 0.55, 0.40, 0.84, 0.91, 0.39, respectively). The changes in OCTA thickness values failed to predict VF MD progression in the superior, inferior,nasal,temporal,and total quadrants (p = 0.40, 0.11, 0.24, 0.44, 0.10, respectively). The changes in OCTA RPCP values ​​did not show superiority in the ability to predict RNFL progression in superior, inferior, nasal, temporal, and total quadrants (p = 0.21, 0.53, 0.39, 0.39, 0.29, respectively). The changes in OCTA RPCP values ​​did not show superiority in the ability to predict VF progression in superior, inferior, nasal, temporal, and total quadrants (p = 0.96, 0.29, 0.77, 0.42, 0.21, respectively). Conclusion: Although OCTA is a non-invasive imaging test whose use and popularity have been increasing in recent years, our study could not show superiority compared to RNFL and VF tests in demonstrating glaucoma progression.